Effect Of Ciprofloxacin And Resveratrol Combination On Expression of pelA , pslD, mexA Genes of Pseudomonas aeruginosa isolates from lower respiratory tracts. - Sattar, Samaa Salman; Kareem Ibrahim Mubarak (ASJ - Academic Science Journal, 2025)
A total of 200 sputum specimens were collected from the patients infection with Lower Respiratory Tract ( LRT) who attended Baquba Teaching Hospital and Chest Diseases Center Baquab city /Iraq. The study aimed to investigate the effect of resveratrol as efflux pumps inhibitor on ciprofloxacin MIC and compare the effect of two agents on expression of pelA , pslD, mexA genes for P. aeruginosa isolates ,all specimens were inoculated on suitable media for isolation and identification of bacteria by morphological , biochemical tests and molecular diagnosis using the polymerase chain reaction .The results showed that overall prevalence of P. aeruginosa among patients was 24 (12%) isolates were identified .The percentages of the phenotypic detection haemolysin test , pyocinin pigment 100 % and 95.83% respectively. Our study reveal that sub-MIC of Resveratrol cause reduction in MIC of Ciprofloxacin for most isolates, . The combination effect of of resveratrol and Ciprofloxacin on the expression of Biofilms formation genes pelA, psID and efflux pump gene mexA revealed a synergistic impact were cause a reduction in mean of gene expression of this three genes ( 0.45 , 0. 60 . 0.90 ) respectively in three MDR P. aeruginosa isolates.